Public Health and Cost Benefits of Successful Reperfusion After Thrombectomy for Stroke. Issue 3 (March 2020) - Kunz, Wolfgang G.; Almekhlafi, Mohammed A.; Menon, Bijoy K.; Saver, Jeffrey L.; Hunink, Myriam G.; Dippel, Diederik W.J.; Majoie, Charles B.L.M.; Liebeskind, David S.; Jovin, Tudor G.; Davalos, Antoni; Bracard, Serge; Guillemin, Francis; et al.
Abstract : Background and Purpose—: The benefit that endovascular thrombectomy offers to patients with stroke with large vessel occlusions depends strongly on reperfusion grade as defined by the expanded Thrombolysis in Cerebral Infarction (eTICI) scale. Our aim was to determine the lifetime health and cost consequences of the quality of reperfusion for patients, healthcare systems, and society. Methods—: A Markov model estimated lifetime quality-adjusted life years (QALY) and lifetime costs of endovascular thrombectomy–treated patients with stroke based on eTICI grades. The analysis was performed over a lifetime horizon in a United States setting, adopting healthcare and societal perspectives. The reference case analysis was conducted for stroke at 65 years of age. National health and cost consequences of improved eTICI 2c/3 reperfusion rates were estimated. Input parameters were based on best available evidence. Results—: Lifetime QALYs increased for every grade of improved reperfusion (median QALYs for eTICI 0/1: 2.62; eTICI 2a: 3.46; eTICI 2b: 5.42; eTICI 2c: 5.99; eTICI 3: 6.73). Achieving eTICI 3 over eTICI 2b reperfusion resulted on average in 1.31 incremental QALYs as well as healthcare and societal cost savings of $10 327 and $20 224 per patient. A 10% increase in the eTICI 2c/3 reperfusion rate of all annually endovascular thrombectomy–treated patients with stroke in the United States is estimated to yield additional 3656 QALYs and save $21.0 million and $36.8 million for the healthcare system and society, respectively. Conclusions—: Improved reperfusion grants patients with stroke additional QALYs and leads to long-term cost savings. Procedural strategies to achieve complete reperfusion should be assessed for safety and feasibility, even when initial reperfusion seems to be adequate. Abstract : Supplemental Digital Content is available in the text.